Improving Learning Outcomes of Straight Line Equations by Applying the Problem-Based Learning (PBL) Model with a Scientific Approach for Class VIII.A Student of SMPN 3 Kendari - Rini Indrawati (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2023)
This study aims to determine whether using the problem-based learning (PBL) model with a scientific approach can improve the learning outcomes of straight-line equations in Class VIII. A student of SMP Negeri 3 Kendari in the 2022/2023 Academic Year. The research subjects were students of class VIII. An SMP Negeri 3 Kendari, the number of students in this class was 30, consisting of 13 boys and 17 girls. This research was conducted in two cycles, each cycle using the steps of (1) planning, (2) implementation, (3) observation, and (4) reflection. The data obtained were analyzed using descriptive statistics. Based on data analysis, the implementation of the actions in cycle I showed that the average class value was 69.53, and the percentage of classical completeness was 46.67%. This result has yet to reach classical completeness of 65% or more. Observing student learning activities in the cycle, I found that the average score of student learning activities was 71.5, which was classified as less active. The results of the cycle research showed that student achievement was still lacking and student learning activity was still low. After improving the learning process, the analysis results in cycle II obtained an average class value of 74.60 and a classical completeness percentage of 86.67%. The results of observing student learning activities obtained an average score of student activity of 90.5%, which is classified as active. Â